Long-term athlete development - Balyi, Istvan; Way, Richard 1957-; Higgs, Colin 1945- (Human Kinetics, 2013)
Describes how to systematically develop sporting excellence and increase active participation in local, regional and national sport organisations. This title describes the long-term athlete development model, an approach to athlete-centered sport that combines skill instruction with long-term planning and an understanding of human development.